Workflow analysis for self-Adaptive agent-based simulation model - Loo Y.L.; Tang A.Y.C.; Ahmad A.; Mustapha A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Modal analysis; Robotics; Case-studies; Document analysis; interview; Self-adaptive agents; Work-flows; Multi agent systems